Variability of T2-Relaxation Times of Healthy Lumbar Intervertebral Discs is More Homogeneous within an Individual Than across Healthy Individuals - Sharma, A.; Walk, R.E.; Tang, S.Y.; Eldaya, R.; Owen, P.J.; Belavy, D.L. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: When one uses T2 relaxometry to classify lumbar intervertebral discs as degenerated, it is unclear whether the normative data should be based on other intervertebral discs from the same individual or from a pool of extraneous controls. This study aimed to explore the extent of intra- versus intersubject variation in the T2 times of healthy intervertebral discs.MATERIALS AND METHODS: Using prospectively acquired T2-relaxometry data from 606 intervertebral discs in 101 volunteers without back pain (47 men, 54 women) in a narrow age range (25–35 years), we calculated intra- and intersubject variation in T2 times of intervertebral discs graded by 2 neuroradiologists on the Pfirrmann scale. Intrasubject variation of intervertebral discs was assessed relative to other healthy intervertebral discs (Pfirrmann grade, ≤2) in the same individual. Multiple intersubject variability measures were calculated using healthy extraneous references ranging from a single randomly selected intervertebral disc to all healthy extraneous intervertebral discs, without and with segmental stratification. These variability measures were compared for healthy and degenerated (Pfirrmann grade ≥3) intervertebral discs.RESULTS: The mean T2 values of healthy (493/606, 81.3%) and degenerated intervertebral discs were 121.1 ± 22.5 ms and 91.5 ± 18.6 ms, respectively (P < .001). The mean intrasubject variability for healthy intervertebral discs was 9.8 ± 10.7 ms, lower than all intersubject variability measures (P < .001), and provided the most pronounced separation for healthy and degenerated intervertebral discs. Among intersubject variability measures, using all segment-matched healthy discs as references provided the lowest variability (P < .001).CONCLUSIONS: Normative measures based on the T2 times of healthy intervertebral discs from the same individual are likely to provide the most discriminating means of identifying degenerated intervertebral discs on the basis of T2 relaxometry.I, X, Xs, Xc, Xcsvarious measures of variability in T2 times of intervertebral discsIVDintervertebral discnpused as a suffix to indicate measures assumed to represent nucleus pulposus